1个回答
展开全部
设圆心为(m,n)
则, (m-5)^2+(n-2)^2=(m-3)^2+(n+2)^2=R^2,(1)
且n+2m-3=0 (2)
化简(1)
m^2-10m+25+n^2-4n+4=m^2-6m+9+n^2+4n+4
4m+8n-16=0
m+2n-4=0(3)
由(2),(3)可得。m+2(3-2m)-4=0 m+6-4m-4=0 -3m+2=0
3m-2=0 m=2/3 n=5/3
R^2=(2/3-5)^2+(5/3-2)^2=169/9+1/9=170/9于是所求的方程是
(x-2/3)^2+(y-5/3)^2=170/9
则, (m-5)^2+(n-2)^2=(m-3)^2+(n+2)^2=R^2,(1)
且n+2m-3=0 (2)
化简(1)
m^2-10m+25+n^2-4n+4=m^2-6m+9+n^2+4n+4
4m+8n-16=0
m+2n-4=0(3)
由(2),(3)可得。m+2(3-2m)-4=0 m+6-4m-4=0 -3m+2=0
3m-2=0 m=2/3 n=5/3
R^2=(2/3-5)^2+(5/3-2)^2=169/9+1/9=170/9于是所求的方程是
(x-2/3)^2+(y-5/3)^2=170/9
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询